The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1970
DOI: 10.3329/bjar.v34i2.5791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shade and nitrogen levels on quality Bangladhonia production

Abstract: A field experiment was conducted to determine the optimum shade level and nitrogen fertilizer for quality Bangladhonia (Eryngium foetidum L.) production at the Bangahandhu Sheikh Mujibar Rahman Agricultural University (BSMRAU) Research Farm during December 2002 to May 2003. The treatments consisted of four shade levels (0, 25, 50, and 75% shades) and five nitrogen rates (0, 115, 138, 161, and 184 kg N/ha). Shades were artificially created by using nylon nets of different mesh sizes and colours. Fifty percent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
5
8
0
Order By: Relevance
“…The minimum number of leaves/plant was found in control (N 0 ) treatment in all cases (CS001 and CS003). The results are in agreement with that of Moniruzzaman et al (2009) where maximum number of leaves/plant was found at the highest dose of N in 'Bangladhonia' (Eryngium foetidum L.). The maximum leaves/plant (7.45/plant and 8.22/plant) was recorded from two applications of N, one half at basal and the remaining half at 30 DAS as top dress (M 2 ), which was similar to the application of entire N applied as basal (M 1 ) and one-half N applied at basal and the rest one-half at 30 DAS as foliar spray (M 3 ) in the genotype CS001 and CS003, respectively (Table 1).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The minimum number of leaves/plant was found in control (N 0 ) treatment in all cases (CS001 and CS003). The results are in agreement with that of Moniruzzaman et al (2009) where maximum number of leaves/plant was found at the highest dose of N in 'Bangladhonia' (Eryngium foetidum L.). The maximum leaves/plant (7.45/plant and 8.22/plant) was recorded from two applications of N, one half at basal and the remaining half at 30 DAS as top dress (M 2 ), which was similar to the application of entire N applied as basal (M 1 ) and one-half N applied at basal and the rest one-half at 30 DAS as foliar spray (M 3 ) in the genotype CS001 and CS003, respectively (Table 1).…”
Section: Resultssupporting
confidence: 91%
“…The result is in agreement with the result of BARI (2010) where it was reported that the maximum fresh yield of Batishak was obtained at 80 kg N/ha and no significant difference was observed among 40 and 80 kg N/ha. The result is in partial agreement with Moniruzzaman et al (2009) who found the highest fresh yield of Bangladhonia with the application of the highest dose of nitrogen. The foliage yield showed a linear response with increasing levels of nitrogen (Fig.…”
Section: Foliage Weight Per Square Metersupporting
confidence: 90%
See 1 more Smart Citation
“…This result is coherence with the result of yield of Indian spinach as leaf number, leaf length and the vine length increased higher yield. In earlier study plants grown under shade (50%) with nitrogen application showed vigorous growth and yield compared to open field (unshaded condition) in bangladhonia (Eryngium foetidum) (Moniruzzaman et al, 2009). Similarly, Akther et al (2019) have found that the highest yield of okra was found 57% higher compared to control which was grown under the netting with the nutrient management combination of organic and inorganic fertilizers.…”
Section: Resultsmentioning
confidence: 85%
“…These might be the reasons for highest plant height observed in this shade level throughout the experiment. Moniruzzaman et al, (2009) This might be the fact that plant at this shade level would have received.…”
Section: Plant Heightmentioning
confidence: 99%